Masquerade : essays on tradition and innovation worldwide - Bell, Deborah, 1952- (McFarland & Company, Inc., Publishers, 2015)
In its conventional meaning, masquerade refers to a festive gathering of people wearing masks and elegant costumes. But traditional forms of masquerade have evolved over the past century to include the representation of alternate identities in the media and venues of popular culture, including television, film, the internet, theater, museums, sports arenas, popular magazines and a range of community celebrations, reenactments and conventions. This collection of fresh essays examines the art and function of masquerade from a broad range of perspectives. From African slave masquerade in New Worl.